Laser beam welding of dissimilar joints between austenitic and ferritic stainless steels - Holzer, Matthias; Hugger, Florian; Weigl, Markus; Roth, Stephan; Schmidt, Michael (Welding and Cutting, 2014)
Investigations were conducted regarding laser beam welding of dissimilar joints between austenitic and ferritic stainless high-alloyed steels for applications in the thin sheet range. In this respect, considerable local differences in the chemical resistances of the welds are confronting potential industrial users with great challenges and have prevented a widespread utilisation of these dissimilar joints until now. In order to avoid corrosive defects, an analysis of influences of weld quality was carried out regarding base material, molten pool dynamics and active process gases during laser beam welding. In this case, it was possible to demonstrate that for example the use of small spot diameters (approx. 200 μm) serves to counteract the initiation and propagation of local corrosion in a sustainable way and to ensure that the mixed joints exhibit chemical resistances which are appropriate for the requirements.
CRIS-Team Scopus Importer:2023-03-07